THE COMMUNITY PARTICIPATION IN THE MANAGEMENT OF DRINKING WATER FACILITIES IN LANGAM VILLAGE, LOPOK DISTRICT SUMBAWA REGENCY - Suryani, Erma Hadi; Saleh, Muhammad; Fietroh, M. Nur (Akademi Komunitas MAPINDO, 2022)
This study discusses the community Participation in the Management of Drinking Water Facilities in Langam Village, Lopok District Sumbawa Regency. The objectives of this research consist of; 1) to find out community participation in the management of drinking water facilities in Langam village, Lopok sub-district, Sumbawa Regency and 2) to find out supporting and inhibiting factors in community participation in Langam village, Lopok sub-district Sumbawa Regency. The approach used in this research is a qualitative descriptive approach. This research was conducted in Langam village, Lopok district Sumbawa Regency. Collecting data using interview methods, and documentation. Furthermore, the data analyzed consisted of three activity procedures, namely; data reduction, data presentation and data verification or conclusions. The results of the study found that community participation in drinking water management in Langam Village, Lopok District Sumbawa Regency was divided into two forms, namely; viewed from the planning stage of the development of drinking water facilities, it is measured by looking at three items consisting of a) the activity of residents attending meetings; b) submit proposals or opinions; and c) Participation in decision making. Then, in terms of the stages of Development of Drinking Water Facilities, it was found based on the items; a) manpower, b) financing, c) materials, and d) thoughts. Furthermore, the supporting factors for the level of community participation consist of factors of ability, willingness, and opportunity. Furthermore, the factors that hinder the low community participation in drinking water management in Langam village include; individual nature factors, economy, age, and education. The implementation of the management of drinking water facilities is carried out in 3 stages, namely: 1) In operating services, the form of community participation is in the form of financing and manpower for the operation of machine operations. 2) Community participation in maintaining drinking water facilities in the form of energy, materials and thoughts during routine cleaning, monitoring water networks, draining sedimentation wells, and cleaning reservoirs. 3) Community participation in repairs in the form of manpower, financing, materials and thoughts such as repairing leaking pipes and others, cleaning machines together. Keywords: Community, Participatory, and Management